Analysis of the Performance of the Sub-District Government in Public Services in Lamuru Sub-District, Bone Regency - Sakir, Ahmad Rosandi; Almahdali, Humairah; Amaliah, Yusriah (Indonesian Scientific Publication, 2023)
The quality of public services provided by government bureaucracy has significantly fallen short of expectations, particularly when considering accountability, responsibility, service orientation, and effectiveness. One of the evident issues is the apparent negligence towards the importance of service users in the implementation of public services. Given the analyzed background problems, the primary research question revolves around understanding the performance of the government sub-district Lamuru in delivering public services. To address this question, the research aims to investigate the performance of the government sub-district Bone in public services and identify the determining factors influencing this performance. The study employs a descriptive-analytic technique for treatment and analysis. The data sources for this research include civil servants working in the sub-district Lamuru office and members of the public. The selection of data sources utilizes random sampling, resulting in a sample size of 80 individuals. Upon analyzing the data, the research concludes that the service quality from the apparatus performance in the sub-district Lamuru is deemed good, yet there is still room for improvement to optimize the overall effectiveness of public services.